School Principals Perspectives in 21st Century; Narrative Study with Reverence to Teachers and Students - Sonia Gul; Dr.Maksal Minaz; Dr. Muhammad Idris, (Dialogue Social Science Review (DSSR), 2025)
The current qualitative study focused on the managerial challenges of secondary school Principals regarding teachers and students. The research questions of the study were; what challenges do Principals face when managing teachers and students in a school at secondary level in district Mardan? How do Principals deal with challenges reverence to teachers and students at secondary level in district Mardan? The research participants of the study included all of the Principals of Government High Schools (boys and girls) in District Mardan. Six respondents were specifically chosen, three from government girls' high schools and three from government boys' high schools in the Mardan district. The research questions of the study formed the basis for the development of a semi-structured interview protocol. A face-to-face interview was carried out with the respondents' permission. The study's trustworthiness was assessed based on credibility, dependability, transferability, and confirmability. Semi-structured interview data was examined using thematic analysis. The thematic analysis revealed that secondary school principals encountered several challenges in controlling and monitoring teachers and students at their institutions. Some of the main challenges included a lack of teachers, high student absenteeism, and poor academic performance. Several Principals, however, made outstanding attempts to resolve the difficulties. Based on the findings, it was recommended that policymakers better grasp the responsibilities and challenges that Principals confront, as well as provide suggestions on how to assist them in successfully managing teachers and students in their schools.